The effect of emergency conditions theory on istisna’a contract - Alkharraz, AbdalRahman Ebrahim (Journal of Social Sciences (COES&RJ-JSS), 2020)
This paper deals with the theory of emergency conditions and their impact on the contract of Istisna’a. It aims to explain this term, its evidence, what is its conditions, and a statement of the Istisna’a contract, the difference and its adaptation.